Kinetic Resolution of 5-Substituted Cyclohexenols by Palladium-Catalyzed Asymmetric Redox-Relay Heck Reaction - Li, Hao; Gao, Ang; Liu, Xiu-Yan; Ding, Chang-Hua; Xu, Bin; Hou, Xue-Long (Synthesis, 2017)
The kinetic resolution of 2-substituted-cyclohexenols via palladium-catalyzed asymmetric redox-relay Heck reaction was realized, providing optically active 2-substituted cyclohexenols and trans-3,5-disubstituted cyclohexan-1-ones in high yield and good enantioselectivities with an S factor up to 22.
Keywords: palladium; Heck reaction; kinetic resolution; cyclohexenol; cyclohexanone